LABOR BRIEFING PAPER (Tufts Archival Research Center, 2007)
Confidential; Memorandum from Howard Liebengood to Fred Panzer regarding a labor meeting briefing paper. Emphasizes the effects of legislation on the tobacco industry and on labor unions.